Quality factor inversion applied to 3D seismic data in Colombia (2017)
Seismic attenuation, usually quantifed by the dimensionless parameter Q, contains valuable information of the petrophysical parameters of the subsurface, and presents a valuable tool for reservoir characterization. Yet, due to the number of issues that must be addressed to obtain reliable measurements, it is rarely calculated. In this work I present a robust method to calculate attenuation on the "tau"- p domain from prestack CMP gathers. The PSQI method Reine (2009), uses a variable-window timefrequency transform, a simultaneous inversion scheme, and a "tau"- p domain transform to get an accurate attenuation measurement in the form of 1/Q. To test the robustness of the method, I apply the PSQI to a 3D dataset from Colombia. Before doing the inversion, I describe a step by step preproccesing that must be done to improve the attenuation measurements, and reduce the uncertainty of the inversion. The final result proves the reliability of the PSQI method